Self‐administration of methamphetamine alters gut biomarkers of toxicity. (August 2017) - Flack, Amanda; Persons, Amanda L.; Kousik, Sharanya M.; Celeste Napier, T.; Moszczynska, Anna
Abstract: Methamphetamine (METH) is a highly abused psychostimulant that is associated with an increased risk for developing Parkinson's disease (PD). This enhanced vulnerability likely relates to the toxic effects of METH that overlap with PD pathology, for example, aberrant functioning of α‐synuclein and parkin. In PD, peripheral factors are thought to contribute to central nervous system (CNS) degeneration. For example, α‐synuclein levels in the enteric nervous system (ENS) are elevated, and this precedes the onset of motor symptoms. It remains unclear whether neurons of the ENS, particularly catecholaminergic neurons, exhibit signs of METH‐induced toxicity as seen in the CNS. The aim of this study was to determine whether self‐administered METH altered the levels of α‐synuclein, parkin, tyrosine hydroxylase (TH), and dopamine‐β‐hydroxylase (DβH) in the myenteric plexus of the distal colon ENS. Young adult male Sprague‐Dawley rats self‐administered METH for 3 h per day for 14 days and controls were saline‐yoked. Distal colon tissue was collected at 1, 14, or 56 days after the last operant session. Levels of α‐synuclein were increased, while levels of parkin, TH, and DβH were decreased in the myenteric plexus in the METH‐exposed rats at 1 day following the last operant session and returned to the control levels after 14 or 56 days of forced abstinence. The changes were not confined to neurofilament‐positive neurons. These results suggest that colon biomarkers may provide early indications of METH‐induced neurotoxicity, particularly in young chronic METH users who may be more susceptible to progression to PD later in life. Abstract : Methamphetamine (METH) abuse is associated with an increased risk for developing Parkinson's disease (PD). The pathology link between METH abuse and PD is unknown. The gut is involved in early stage PD, and here, we reveal that several PD toxicity markers (tyrosine hydroxylase (TH), dopamine‐β‐hydroxylase (DβH), parkin, and α‐synuclein) in the myenteric plexus of the distal colon are altered in rats with a history of METH self‐administration in an abstinence duration‐dependent manner. Thus, colonic markers may help identify METH users who are vulnerable to developing PD later in life.